Mobile Apps in Daily Learning Activities - Damyanov, Ivo; Tsankov, Nikolay (International Journal of Interactive Mobile Technologies (iJIM), 2018)
The use of mobile devices is increasing in daily learning activities, providing single-person use combined with interactive learning materials, simulations, voice recognition and educational games. Mobile app stores bring to learners a large amount of mobile applications, but their value and effectiveness to support these learning activities is far from being adequately studied. In this paper, we present our recent study related to the opportunities for smart devices to be used in school education, outlining the main obstacles and challenges. The subject of the research is students’ interest in the use of multimedia mobile devices for educational purposes. The aim of the study is to establish the main determinants for the complete and purposeful application of smart devices in school education.